A Plasmodium Gene Family Encoding Maurer's Cleft Membrane Proteins: Structural Properties and Expression Profiling - Sam-Yellowe, Tobili Y.; Florens, Laurence; Johnson, Jeffrey R.; Wang, Tongmin; Drazba, Judith A.; Le Roch, Karine G.; Zhou, Yingyao; Batalov, Serge; Carucci, Daniel J.; Winzeler, Elizabeth A.; Yates, John R. (Genome Research, 2004)
Upon invasion of the erythrocyte cell, the malaria parasite remodels its environment; in particular, it establishes a complex membrane network, which connects the parasitophorous vacuole to the host plasma membrane and is involved in protein transport and trafficking. We have identified a novel subtelomeric gene family in Plasmodium falciparum that encodes 11 transmembrane proteins localized to the Maurer's clefts. Using coimmunoprecipitation and shotgun proteomics, we were able to enrich specifically for these proteins and detect distinct peptides, allowing us to conclude that four to 10 products were present at a given time. Nearly all of the Pfmc-2tm genes are transcribed during the trophozoite stage; this narrow time frame of transcription overlaps with the specific stevor and rif genes that are differentially expressed during the erythrocyte cycle. The description of the structural properties of the proteins led us to manually reannotate published sequences, and to detect potentially homologous gene families in both P. falciparum and Plasmodium yoelii yoelii, where no orthologs were predicted uniquely based on sequence similarity. These basic proteins with two transmembrane domains belong to a larger superfamily, which includes STEVORs and RIFINs.